Kebutuhan Sumber Belajar Mahasiswa yang Mendukung Pembelajaran Berbasis Teknologi Informasi dan Komunikasi di Perguruan Tinggi - Imam Fitri Rahmadi; Khaerudin Khaerudin; Cecep Kustandi (Jurnal Teknologi Pendidikan)
This study is aimed at gathering information about the tendency of learning resources needed by the students of Universitas Negeri Jakarta (UNJ) that support ICT based learning. The study is conducted using the survey method applying questionnaires that randomly distributed to the students. The questionnaires filled in by 580 students of 22 different study programmes covering six faculties of UNJ. Every faculty tends to have different learning resources. However, videos are the most essential learning resources needed by students. The development of learning resources in higher education must consider the need of learning resources of students of each faculty, not the university as a whole.